Niektóre społeczno-gospodarcze i polityczne uwarunkowania procedury podatkowej - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 1982)
The body of regulation of fiscal proceedings is to a large extent a reflection not only of the current trends of State's taxation policy but also of the tasks to be realized in that matter in some pre-described long-run prospects. The policy towards the unsocialized units of economy and private persons is influenced by the socio-economic and political premises. Whenever the taxation policy making has been biased by the structural premises of the political system and the socio-economic aspect of the problem — dominated by it, both the legal regulation and the practice adopted the extreme shape. The fiscal policy formed under the powerful structural influence of the socialistic system was only a natural outcome. Collecting exorbitant and often unjustified taxes and charges was supposed to secure certain goals, e.g. in the sphere of limiting the developement of the unsocialized economy. On account of the adopted institutional solutions, the regulation of fiscal proceedings could not guarantee a proper protection of taxpayer's legal interests in the tax proceedings. Some liberalization in the regulation of the procedure in the aspect of both: legislation and application can be noticed whenever the unsocialized sector of economy is viewed mainly through certain economic principles and social goals while the political aspects of it can fade away in the background. The shape of taxation proceedings defined by the body of its legal regulation has to account for socio-economic and political conditioning not only at the moment of legislation but also in the long run prospects.
Some Aspects of Socio-Economic and Political Conditioning of the Fiscal Proceedings